Frontal Fibrosing Alopecia with Lichen Planus Pigmentosus – Two Case Reports - Paniagua, D. C.; Santos, T. S.; Jeunon, T. S. V.; Marques-Da-Costa, J. C.; Melo, D. F. (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Frontal fibrosing alopecia, a variant of lichen planopilaris, was first described by Kossard in 1994. It consists of a cicatricial alopecia characterized by progressive rarefaction of frontotemporal implantation line. Dermoscopy has a great importance to improve diagnosis accuracy and is a relevant tool to distinguish it from other differential diagnosis. Lichen planus pigmentosus is another variant of lichen planus, of uncommon occurrence, that specially affects women with phototypes III and IV, between third and fourth decades of life. In this article, two cases of the rare association of Lichen planus pigmentosus and frontal fibrosing alopecia are reported in two female patients, aged 59 and 76 years melanodermic women, presenting frontotemporal margin hair loss and brown hyperpigmentation on the face, neck and trunk.